Individual Differences in Subjective Utility and Risk Preferences: The Influence of Hedonic Capacity and Trait Anxiety - Howlett, Jonathon R.; Paulus, Martin P. (Frontiers in Psychiatry, 2017)
Individual differences in decision-making are important in both normal populations and in psychiatric conditions. Variability in decision-making could be mediated by different subjective utilities or by other processes. For example, while traditional economic accounts attribute risk aversion to a concave subjective utility curve, in practice other factors could affect risk behavior. This distinction may have important implications for understanding the biological basis of variability in decision-making and for developing interventions to improve decision-making. Another aspect of decision-making that may vary between individuals is the sensitivity of subjective utility to counterfactual outcomes (outcomes that could have occurred, but did not). We investigated decision-making in relation to hedonic capacity and trait anxiety, two traits that relate to psychiatric conditions but also vary in the general population. Subjects performed a decision-making task in which they chose between low- and high-risk gambles to win 0, 20, or 40 points on each trial. Subjects then rated satisfaction after each outcome on a visual analog scale, indicating subjective utility. Hedonic capacity was positively associated with the subjective utility of winning 20 points, but was not associated with the concavity of the subjective utility curve (constructed using the mean subjective utility of winning 0, 20 or 40 points). Consistent with economic theory, concavity of the subjective utility curve was associated with risk aversion. Hedonic capacity was independently associated with risk seeking (i.e. not mediated by the shape of the subjective utility curve), while trait anxiety was unrelated to risk preferences. Contrary to our expectations, counterfactual sensitivity was unrelated to hedonic capacity and trait anxiety. Nevertheless, trait anxiety was associated with a self-report measure of regret-proneness, suggesting that counterfactual influences may occur via a pathway that is separate from immediate counterfactual processing biases. Taken together, our results show that hedonic capacity but not trait anxiety affects risk-taking through a mechanism that appears independent of the shape of the subjective utility curve, while hedonic capacity and trait anxiety do not affect the influence of counterfactual outcomes on subjective utility. The results have implications for understanding the underlying mechanisms of variable decision-making and for developing interventions to improve decision-making.